School Bus Routing Problems and Solutions for Smart Cities - Ochoa, Alberto (Taylor & Francis Group, 2019)
Among the major concerns within the cities, are related to the problems of vehicular transport. The SBRP application seeks to improve the movement routes. Bus service to schools is a strategy to reduce costs, provide security to students and arrive on time to their destinations. In this book chapter, the authors have discussed the issues related to the school bus routing problem. At the end authors also proposed a dynamic model associated with the School Bus Algorithm for the competitive improvement of a smart city using ubiquitous computing. A new PSO algorithm is proposed to improve and solve the problem of the routing school bus. The results allow knowing different routes for the mobility of students, the visualization using a mobile device as an auxiliary in the logistical support of the school can provide better results to be able to determine the exact points of travel of the school transport, and define the best routes for the service.